New Gushing Mechanism Proposed by Applying Particle Size Analysis and Several Surfactants - Christian, Manuel; Ilberg, Vladimír; Aydin, Ahmet Alper; Titze, Jean; Friess, Albrecht; Jacob, Fritz; Parlar, Harun (BrewingScience, 2009)
The complex phenomenon of gushing occurring in carbonized beverages has been investigated in order to better understand the mechanism and to give input for further research to introduce preventive measures for the industry. The knowledge that microbubbles are stabilized through surface active substances, and in this form can induce gushing, was used to examine a selection of representative surfactants. For the analysis, a particle size distribution method was used which enabled to detect particles at nanometer level, starting from 0.8 nm onwards. The experiments using pure aliphatic surfactants (DTAC, TTAC, CTAC, ODTABr, CPC, SDS, and Tween 20) revealed that only CTAC, solved in CO2 containing table water at 2 g/l (above the critical micellar concentration), induced gushing. CTAC therefore was characterized as gushing typical by its structure (length of hydrophobic part and kind of head group). Gushing caused by CTAC was not only observed through shaking of the bottles, but also without any shaking at all. The latter observed fact was not explainable by the mechanical incorporation of CO2 bubbles stabilized by CTAC monomers, but generally through stabilized microbubbles formed by a mechanism that is yet unknown. The particle size analysis revealed that particles grow, starting from ca. 10 nm to reach several 100 nm, if sufficient amounts of CO2 molecules are present. The growth was accelerated by a mild shaking of the bottles. The results pointed out that CTAC micelles grow by diffusion of CO2 molecules into the hydrophobic core. Thereby, microbubbles are formed and stabilized through CTAC monomers at the interface gas/liquid, and can grow to gushing-relevant sizes of several 100 nm.